Stonehenge and Avebury: Megalithic shadow casting at the solstices at sunrise - G. Terence Meaden (Journal of Lithic Studies, 2017)
The paper examines how specific megaliths at Stonehenge and Avebury were positioned relative to others and to particular sunrises such as to produce watchable effects arising from solar movement and resulting lithic shadows. At Stonehenge and environs numerous research expeditions (exceeding 120 that started in 1981) combined with accurate compass analysis, photography and studies of the best plans of the sarsen-stone and bluestone phases have led to explanations for apparent anomalies of stone positioning that have not been clarified before.